The role of the rules of customary international humanitarian law in protecting the natural environment (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The rules of customary international humanitarian law contribute to mitigating the severity of damage to the natural environment resulting from military operations by providing the minimum principles of humanitarian concern that should be taken into account in armed conflicts whether international or no international, this is based on the consideration of the global environment as a common heritage of humanity, it is also applied at all times and every place as it is accepted by members of the international community, whether they are parties to humanitarian agreements or not thus it supports the legal protection of the environment during armed conflicts and fills some of the gaps included in this protection, the protection of the natural environment from the effects military operation is manifested under a set of general customary rules that seek to make the effects of the group more humane in addition to the customary rules for protecting the natural environment during armed conflicts.